Evaluation of hepatitis B virus antibodies in serum in vaccinated children at Tishreen University Hospital in Syria - Wassouf, Reem Faez; Zreik, Youssef Amin (Journal of medical and pharmaceutical sciences, 2022)
Background: This study was done to evaluate the level of serum antibody titers in children vaccinated for HBV at Tishreen University Hospital, and to compare the titers of anti-HBs between the different age groups. This study also aimed to evaluate the relation between the infant feeding type and the response to the vaccine.Materials and Methods: A total of 170 children aged 1-12 years including 73 girls and 97 boys were gathered from pediatric department in Tishreen University Hospital. All the children in this study have undergone hepatitis B vaccine program according to the national standards (3 doses at 0, 1, 6 months after birth). The study sample was distributed into three groups according to age as follow: Group1 included children aging [1-4] years, Group2 included children aging [5-8] years, and Group3 included children aging [9-12] years. Plasma anti-HBs titers were measured. In the first age group, it was studied the response rate, and effects of both gender and infant feeding type on immune response to the vaccine. between response due to vaccination and that due to past infection.Results: Children who had a titer higher than 10 miu/mL were considered as responders. Our results revealed that the response rate was (81.1%). No significant difference was observed in antibody concentration between groups 1 and 2 (P=0.14). However, significant statistical difference was observed between groups 2 and 3 (P=0.0009), and between groups 1 and 3 (P=0.01). There was no signifi¬cant difference between girls and boys regarding the response rate (P = 0.65). On the other hand, the statistical analysis showed that there was no relation between the infant feeding type and the response rate. (P=0.96).Conclusion: The response rate to HBV vaccine in our study was 81.1%, which is less than the expected international rate (90-95%). Significant relation was observed between age and waning of antibody titer. However, no statistically significant difference was observed between type of infant feeding and response to HBV vaccine.
Keywords: Hepatitis B virus; HBV vaccine; anti HBs; response rate